Atrial deformation correlated with functional capacity in mitral stenosis patients. Issue 2 (11th December 2017) - Chien, Chen‐Yu; Chen, Chih‐Wei; Lin, Tin‐Kwang; Lin, Yu; Lin, Jnnu‐Wen; Li, Yi‐Da; Chen, Chi‐Hsien; Tsai, Wei‐Chuan
Abstract : Background: Left atrial (LA) dysfunction, expressed as impaired LA deformation using two‐dimensional (2D) strain imaging, has been observed in association with rheumatic mitral stenosis (MS). However, the clinical role of speckle tracking echocardiography (STE)‐derived LA strain has rarely been studied in MS. Aim: This study aimed to identify the determinants of New York Heart Association (NYHA) functional class in patients with mitral stenosis and to investigate the relationship between left atrial deformation as measured by two‐dimensional STE‐derived LA strain and heart failure symptoms. Methods: Sixty‐nine consecutive patients (20 males and 49 females; mean age: 61 ± 14 years) with rheumatic MS were evaluated using comprehensive 2D and color Doppler echocardiography including STE‐derived LA strain (LAS) and peak positive filling strain rate (LASRr) during the LA reservoir phase. Those results were then correlated with NYHA functional class. Results: There were 15 (22%) patients in functional class I, 42 (61%) in functional class II, and 12 (17%) in functional class III. There were no significant differences in mitral valve area, pressure gradient, pulmonary artery pressure, LA emptying fraction, or left ventricular ejection fraction between functional classes. Upon multivariate analysis (controlling for diuretics usage), LAS (ß = −0.233, P = .045) and LASRr (ß = −0.277, P = .014) were independent factors in determining NYHA functional class. Conclusions: In stable patients with MS, NYHA functional class independently correlated with LAS and LASRr. Left atrial (LA) deformation correlated with heart failure symptoms in patients with MS.